Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve [tex][tex]$6+\sqrt[5]{249-2x}=7$[/tex][/tex].

Show your work.


Sagot :

Sure, let's solve the equation [tex]\( 6 + \sqrt[5]{249 - 2x} = 7 \)[/tex] step by step.

1. Isolate the radical:
We start by isolating the fifth root term on one side of the equation. To do this, we can subtract 6 from both sides of the equation:
[tex]\[ 6 + \sqrt[5]{249 - 2x} - 6 = 7 - 6 \][/tex]
Simplifying this:
[tex]\[ \sqrt[5]{249 - 2x} = 1 \][/tex]

2. Eliminate the radical:
Next, we need to get rid of the fifth root by raising both sides of the equation to the power of 5:
[tex]\[ \left(\sqrt[5]{249 - 2x}\right)^5 = 1^5 \][/tex]
This simplifies to:
[tex]\[ 249 - 2x = 1 \][/tex]

3. Solve for [tex]\( x \)[/tex]:
Now, we solve for [tex]\( x \)[/tex]. Start by isolating the term that contains [tex]\( x \)[/tex]:
[tex]\[ 249 - 2x = 1 \][/tex]
Subtract 249 from both sides:
[tex]\[ -2x = 1 - 249 \][/tex]
Simplify the right-hand side:
[tex]\[ -2x = -248 \][/tex]
Finally, divide both sides by -2:
[tex]\[ x = \frac{-248}{-2} \][/tex]
Simplifying this gives:
[tex]\[ x = 124 \][/tex]

Thus, the solution to the equation [tex]\( 6 + \sqrt[5]{249 - 2x} = 7 \)[/tex] is [tex]\( x = 124 \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.